Safety and efficacy of voxelotor in pediatric patients with sickle cell disease aged 4 to 11 years. Issue 8 (21st April 2022) - Estepp, Jeremie H.; Kalpatthi, Ram; Woods, Gerald; Trompeter, Sara; Liem, Robert I.; Sims, Kacie; Inati, Adlette; Inusa, Baba P. D.; Campbell, Andrew; Piccone, Connie; Abboud, Miguel R.; Smith‐Whitley, Kim; et al.
Abstract: Background: Sickle cell disease (SCD) is a devastating, multisystemic disorder that affects millions of people worldwide. The earliest clinical manifestations of SCD can affect infants as young as 6 months of age, and pediatric patients are at risk for acute and life‐threatening complications. Early intervention with treatments that target the underlying pathophysiological mechanism of SCD, sickle hemoglobin (HbS) polymerization, are expected to slow disease progression and circumvent disease‐associated morbidity and mortality. Procedure: The HOPE‐KIDS 1 trial (NCT02850406) is an ongoing four‐part, phase 2a, open‐label, single‐ and multiple‐dose study to evaluate the pharmacokinetics, efficacy, and safety of voxelotor—a first‐in‐class HbS polymerization inhibitor—in patients aged 6 months to 17 years with SCD. Initial findings from a cohort of 45 patients aged 4 to 11 years who received voxelotor treatment for up to 48 weeks are reported. Results: Hemoglobin (Hb) response, defined as a >1.0 g/dl increase from baseline, was achieved at week 24 by 47% ( n = 16/34) of patients with Hb measurements at baseline and week 24. At week 24, 35% ( n = 12/34) and 21% ( n = 7/34) of patients had a >1.5 g/dl increase and a >2.0 g/dl increase from baseline in Hb concentration, respectively. Concurrent improvements in hemolytic markers were observed. Voxelotor was well tolerated in this young cohort, with no newly emerging safety signals. Conclusions: Based on its mechanism as an HbS polymerization inhibitor, voxelotor improves Hb levels and markers of hemolysis and has the potential to mitigate SCD‐related complications; these results support its use in patients aged ≥4 years.